Original paperBreast conservation therapy without capsular contracture in young augmented women using interstitial brachytherapy - Kuske, Robert (Journal of Contemporary Brachytherapy, 2014)
Purpose : To describe a breast-conserving technique using interstitial brachytherapy after lumpectomy and axillary nodal sampling in selected women who are diagnosed with breast cancer in the presence of augmentation mammoplasty. Material and methods : Over the past 20 years, we have developed and improved a technique of “pinch view” image- guided catheter insertion that avoids implant puncture. Selection criteria include: 1) women of any age with either subpectoral or retroglandular, augmentation implants (silicone or saline) who were diagnosed with stages Tis, T1, T2, N0, or N1 breast cancer; 2) any pathologic subtype of malignant breast cancer was accepted; 3) microscopic tumor extent < 3 cm; 4) axillary node negative or metastasis to 1 to 3 nodes without extracapsular extension; and 5) surgical margins clear by the NSABP “no ink on tumor” definition. More than 250 women have been successfully treated. Patients were treated with high dose rate Iridium-192 brachytherapy to 34 Gy in 10 or 32 Gy in 8 twice daily fractions. The target volume was the surgical cavity edge with 1.5 to 2 cm margin using 3-D treatment planning systems. Results: The implant technique as currently employed is described. There have been no implant ruptures, and the Planning Treatment Volume (PTV-eval) exhibited at least 90% coverage by the 90% isodose line in the vast majority of cases. Dose Homogeneity Index exceeded 70% in most cases. The maximum skin dose was below the prescription dose in every case. Other than some patients with pre-existing capsular contracture, less than 5% experience new capsular contracture after interstitial brachytherapy. Conclusions : A technique of reliable and reproducible accelerated partial breast irradiation is described that minimizes the risk of capsular contracture by avoiding circumferential dose to the foreign body in the breast.